The Process of Facilitating Knowledge Acquisition and Retention: An Inquiry into Magnetic Poles with Challenging Questions - Okulu, Hasan Zühtü; Ünver, Ayse Oguz (International education studies, 2018)
The current research is to give an example to the inquiry-based science teaching implementations for facilitating knowledge acquisition and retention in a short period of time. Thus, the aim of the research is to transfer of acquired knowledge into different situations using sequential inquiry activities, which have challenging questions for inquiry about what the magnetic pole is and how to discover it. The research was designed as a pre-experimental, one-group pre-test/post-test (N = 65) with a retention-test. Sequential inquiry-based science activities were applied to provide a series of developmentally appropriate experiences and discussions, which concretely scaffold participant's ideas of magnetism. According to the results, the participants interpreted the magnets and magnetic poles regarding their functions. The common view of the participants was that a magnetic pole should be at the ends. This view is associated with upper-lower or internal-external surfaces for a ring magnet. Finally, with a sphere magnet, both upper-lower or internal-external surfaces have lost their functions and the inquiry begins with the question "How to find the poles of a magnet?" In that process, students get to engage and feel that they do not know something that they should know.